Determinants of Increased Risk Coronary Heart Disease in Posbindu PTM Participants in Jayapura - Asriati; Natalia Paskawati Adimuntja (Miracle Journal of Public Health, 2022)
Coronary Heart Disease (CHD) is the leading cause of death in the world. The prevalence of heart disease in Papua Province is 4.3%, while in Jayapura City is 1.6%. The purpose of this study was to determine the determinants of the increased risk of coronary heart disease in PTM posbindu participants in the working area of ​​the Kotaraja Health Center. This design study used a cross-sectional study. The sample is 52 Posbindu PTM participants who are recorded in the SIPTM Offline Form during 2020. The sampling technique uses total sampling. Statistical test using Chi-Square test and Fisher Exact test. A total of 12 people (23.08%) posbindu participants were at high risk of suffering from CHD, as many as 16 people (30.77%) were at moderate risk of suffering from CHD, and as many as 24 people (46.15%) were at low risk of suffering from CHD in the next 10 years. As many as 81.82% of posbindu participants aged 40 years are at high risk and are suffering from CHD in the next 10 years, and 70% of posbindu participants with hypertension are at high risk and are suffering from CHD in the next 10 years. The results of the statistical analysis found that age (p=0.000), gender (0.011), and a history of heart disease (p=0.011) were associated with an increased risk of CHD in PTM Posbindu participants. Factors associated with an increased risk of CHD are age, gender, and history of heart disease. Strengthening the PTM Posbindu needs to be done to monitor a healthy lifestyle, control blood pressure, and nutritional counselling to control unhealthy diets.